La ilaha illallah: Understanding Tawhid and Its Practice in English for Islamic Studies - Salma Faizatun Nuha; Aulia Nasywa Muyassar; Nurhalisa Ismail; Agung Pranoto Kadiatmadja (Jurnal Hadratul Madaniyah, 2026)
This study explores the multidimensional meaning of La ilaha illallah (“There is no god but Allah”) through an analysis of its theological significance, linguistic structure, and pedagogical application within the discipline of English for Islamic Studies (EIS). Using a qualitative descriptive approach based on library research, the study synthesizes insights from classical tafsir, modern linguistic theory, and Islamic educational thought to uncover the epistemological and ethical dimensions of Tawhid. The findings reveal that La ilaha illallah functions simultaneously as a theological declaration, a linguistic construct, and an educational framework. Linguistically, it unites negation and affirmation to form a coherent structure of truth that mirrors divine logic. Theologically, it encapsulates the essence of Tawhid, defining the relationship between belief, knowledge, and moral responsibility. Pedagogically, it serves as a faith-based model for integrating theology into language learning, allowing students to engage critically and spiritually with English as a medium of understanding revelation. By introducing La ilaha illallah as an epistemological foundation for EIS, this study proposes that language instruction rooted in Tawhid can enhance students’ linguistic precision, intercultural competence, and spiritual consciousness. Ultimately, it redefines language learning as a sacred act of intellectual worship, bridging revelation and reason within the holistic framework of Islamic education.